2018
DOI: 10.2741/4619
|View full text |Cite
|
Sign up to set email alerts
|

The role of T cells in the development of Henoch-Schonlein purpura

Abstract: Introduction 3. Characteristics of HSP 4. Involvement of CD4 + T cells in HSP development 4.1. Th1 cells 4.2. Th2 cells 4.3. Th17 cells 4.4. Treg cells 4.5. Tfh cells 5. Key factors affecting CD4 + T cell differentiation as therapeutic targets 6. Conclusions 7. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Traditionally, ITP has been considered a B-cell-mediated disease because antiplatelet antibodies have been detected in the majority of patients [23]. The imbalance of the Tfr/Tfh ratio in peripheral blood has attracted increasing research interest in the immunotherapy of ITP [9,24]. Given that Tfh and Tfr cells are reciprocal and antagonistic regulators of the germinal center (GC) response, the balance of their actions is critical for immune homeostasis [25].…”
Section: Systematic Bioinformatic Analysis Of High-throughput Gene Ex...mentioning
confidence: 99%
“…Traditionally, ITP has been considered a B-cell-mediated disease because antiplatelet antibodies have been detected in the majority of patients [23]. The imbalance of the Tfr/Tfh ratio in peripheral blood has attracted increasing research interest in the immunotherapy of ITP [9,24]. Given that Tfh and Tfr cells are reciprocal and antagonistic regulators of the germinal center (GC) response, the balance of their actions is critical for immune homeostasis [25].…”
Section: Systematic Bioinformatic Analysis Of High-throughput Gene Ex...mentioning
confidence: 99%
“…Many studies have indicated that fluid and cellular immune dysfunctions contribute to HSP pathogenesis. [12][13][14] Some studies have indicated that elevated blood NLR and decreased MPV can be good predictors of HSP in patients with symptoms of gastrointestinal involvement. 15,16 Skin rash and elevated D-dimer levels may also cause GI bleeding.…”
Section: Introductionmentioning
confidence: 99%